Bima Suci and the Modern Human Existential Crisis: A Philosophical Study of Ki Manteb Sudarsono’s Wayang Kulit Performance - Muhtar, Mohamad Khusnial; Yohanes Mai, Adrianus (Sutasoma : Jurnal Sastra Jawa, 2025)
Amid the identity crisis of modern humans due to the dominance of digital culture and globalization, the wayang kulit performance of Bima Suci by Ki Manteb Sudarsono presents a sustained philosophical reflection on the meaning of life, an epistemology of praxis, and spiritual transformation. This study aims to analyze the philosophical meaning contained in the play using qualitative methods and a systematic-reflective philosophical approach. Primary data derive from a video documentation of Ki Manteb’s performance on the Donkgedank YouTube channel (2018), supplemented by Javanese philosophical literature and relevant scholarship. The findings demonstrate that this performance highlights the teachings of Sangkan Paraning Dumadi (the origin and ultimate purpose of existence), an epistemology of praxis (knowledge gained through lived experience), and Bratasena’s transformation into a spiritually mature self. This philosophical message is particularly relevant for modern humans facing existential alienation in the digital era, suggesting that wayang kulit serves not merely as a spectacle but as a contemplative medium for rediscovering an authentic sense of self.